2022
DOI: 10.3390/microorganisms10061220
|View full text |Cite
|
Sign up to set email alerts
|

Biofertilizer: The Future of Food Security and Food Safety

Abstract: There is a direct correlation between population growth and food demand. As the global population continues to rise, there is a need to scale up food production to meet the food demand of the population. In addition, the arable land over time has lost its naturally endowed nutrients. Hence, alternative measures such as fertilizers, pesticides, and herbicides are used to fortify the soil and scale up the production rate. As efforts are being made to meet this food demand and ensure food security, it is equally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(79 citation statements)
references
References 63 publications
1
55
0
2
Order By: Relevance
“…Repeated solarization loops combined with bio fumigation could also suppress soil-borne pathogens and weeds, and lead to increased tomatoes yield [20]. It took two weeks for each solarization season to produce an adequate temperature profile to inactivate various pathogens [21].…”
Section: Resultsmentioning
confidence: 99%
“…Repeated solarization loops combined with bio fumigation could also suppress soil-borne pathogens and weeds, and lead to increased tomatoes yield [20]. It took two weeks for each solarization season to produce an adequate temperature profile to inactivate various pathogens [21].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have shown that the pesticides and fertilizers used in rice cultivation seriously harm the water environment, leaving large amounts of harmful substances in the ecosystem, as well as inducing eutrophication, which can be eliminated to some extent through microbial metabolism (Kong et al, 2022). On the other hand, some strains also settle into the soil, and these microorganisms undertake several important ecosystem functions including soil carbon and nitrogen cycling, helping to alleviate problems such as reduced soil fertility and soil consolidation caused by rice cultivation (Daniel et al, 2022). The microorganisms that settle into the soil not only improve the soil environment, but a proportion of the bacteria also act as plant growth-promoting rhizobacteria (PGPR) to contribute directly or indirectly to the growth and health effects of rice (Bhattacharyya and Jha, 2012;Hacquard et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Not only do organic fertilisers reduce the demand for fossil fuels, but they also improve soil structure and have been shown to strongly increase the abundance and diversity of nematodes Puissant et al, 2021. Animal manure has been shown to reduce soil bulk density and increase the infiltration and holding capacity of water (Rayne and Aula, 2020). While biofertilisers are microbial inoculations to soil that help to make existing nutrients available for plant uptake (Daniel et al, 2022).…”
Section: Restoration Of Natural Habitatsmentioning
confidence: 99%